State-space modelling approach for control and observer design in property-controlled reverse flow forming - Kersting, Lukas; Arian, Bahman; Rozo Vasquez, Julian; Trächtler, Ansgar; Homberg, Werner; Walther, Frank (IFAC-PapersOnLine)

Mathematik mit Kindern ausgehend von Spiel- und Routinesituationen in der Kindertagesstätte erkunden? - Bruns, Julia; Mette, Tessa (Frühe Bildung)
Zusammenfassung: Frühe mathematische Bildung, die ihren Ausgangspunkt in den (Spiel-)Situationen der Kindertagesstätte nimmt, kann breite mathematische Erfahrungen ermöglichen, wenn die (Spiel-)Situationen entsprechende Möglichkeiten bieten. Erste Studien weisen darauf hin, dass in diesen Situationen verschiedene mathematische Inhalte angesprochen werden können. Allerdings konzentrieren sich bisherige Studien auf ausgewählte Kontexte oder Inhaltsbereiche. Diese Studie zielt daher auf eine vertiefte Analyse der Gelegenheiten für mathematische Erfahrungen, die in verschiedenen (Spiel-)Situationen im Alltag der Kindertagesstätte entstehen können. Dazu wurde eine videobasierte Beobachtungsstudie mittels einer Action-Kamera in einer Kindertagesstätte durchgeführt. Die Ergebnisse zeigen, dass eine Vielfalt von mathematischen Inhalten in (Spiel-)Situationen in der Kindertagesstätte beobachtet werden kann, einzelne Inhalte jedoch nur in formellen Lernsituationen auftreten.

Beethovens Eigenbearbeitungen und digitale Heuristik. Erkundungen mit den synoptischen Doppeleditionen und Analysewerkzeugen des Projekts Beethovens Werkstatt - Münzmay, Andreas

Submatrix and GPU-accelerated implementation of density matrix tight-binding - Katbashev, Abylay; Schade, Robert; Laß, Michael; Müller, Marcel; Grimme, Stefan; Hansen, Andreas; Kühne, Thomas (The Journal of Chemical Physics)
Effective single-particle theories, such as Hartree–Fock, density functional theory, and tight-binding, are limited by the computational cost of the self-consistent field (SCF) procedure, which typically scales cubically with the system size. This makes large-scale applications impractical without specialized algorithms and hardware. Here, we present the submatrix and graphical processing unit (GPU)-accelerated software implementation of the PTB tight-binding potential, realized in the open-source ptb codebase [M. Mueller, A. Katbashev, and S. Ehlert (2025). “grimme-lab/ptb: v3.8.1,” Zenodo. https://zenodo.org/records/17015872]. We first benchmark a traditional diagonalization-based SCF solver against density-matrix-based purification approaches, systematically varying both system size and computer hardware. Our findings show that the usage of GPUs permits shifting the boundaries to much larger systems than previously thought feasible, achieving an overall 10–15-fold performance speedup. Second, we introduce the implementation of a decomposition-type submatrix method, specifically designed for efficient operation on mid- to large-sized systems, to address the computational overhead associated with full-system diagonalization. We demonstrate that, from a certain dimension (≈104 basis functions) on, our submatrix method reduces the overall computational cost while maintaining acceptable numerical accuracy. Our study demonstrates the significance of the interplay between modern hardware, algorithmic considerations, and novel tight-binding methods, paving the way for further development in this direction.

Gratis - Köstliches zwischen den Jahren (Hebr 13,8-9b) 31.12.2025 Silvester/Altjahrsabend - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

Analyse akademischer Selbstkonzepte gewerblich-technischer Lehramtsstudierender unter besonderer Beachtung soziodemographischer Heterogenität und Vergleichsprozessen als Entwicklungseinflüsse - Vernholz, Mats
Selbstkonzepte werden als mentale Repräsentationen einer Person von sich selbst definiert und stehen aufgrund ihrer Bedeutung für den Berufserfolg von (angehenden) Lehrkräften im Fokus der Forschung zur Professionalisierung von Lehrkräften. Ziel der vorliegenden Arbeit ist die de-taillierte Betrachtung der Ausprägungen akademischer Selbstkonzepte von gewerblich-techni-schen Lehramtsstudierenden im Master of Education zur Analyse der Struktur, Entwicklungsein-flüsse und Beziehungen zwischen verschiedenen Dimensionen akademischer Selbstkonzepte anhand eines sequentiellen Mixed-Methods-Designs. Dieses besteht aus einer quantitativen Studie (n=115), angelehnt an das TPACK-Modell, und einer anschließenden qualitativen Inter-viewstudie (n=18) angelehnt an das PCK-Modell. Es zeigt sich, dass akademische Selbstkonzepte angehender Lehrkräfte anhand von Professionswissensmodellen strukturierbar sind. Dies trifft sowohl auf die Strukturierung anhand des TPACK-Modells als auch anhand des PCK-Modells zu. Als Entwicklungseinflüsse zeigen sich besonders Aspekte: praktische Erfahrungen im schulischen sowie im fachwissenschaftlichen Bereich und auch die Auswirkungen sozialer und dimensionaler Vergleichsprozesse. Bei den Auswirkungen von Vergleichsprozessen fungiert jedoch die wahr-genommene Relevanz der jeweiligen Dimensionen der akademischen Selbstkonzepte als Mode-rator. Abschließend werden forschungsmethodische sowie hochschulbildungspraktische Im-plikationen der Ergebnisse diskutiert.

Modular Energy Demand Modeling of Manufacturing Processes for Energy Efficiency Improvement - Naumann, Marius; Henne, Kevin; Ostermann, Moritz; Schlosser, Florian; Meschede, Henning (Procedia CIRP)

STEK Sharing is Not Caring: Bypassing TLS Authentication in Web Servers using Session Tickets - Hebrok, Sven; Storm, Tim Leonhard; Cramer, Felix Matthias; Radoy, Maximilian; Somorovsky, Juraj (34th USENIX Security Symposium (USENIX Security 25))

Efficient shape formation by 3D hybrid programmable matter: An algorithm for low diameter intermediate structures - Hinnenthal, Kristian; Liedtke, David Jan; Scheideler, Christian (Theoretical Computer Science)

Technisches Lernen handwerklich und digital erleben. Eine empirische Untersuchung zur Förderung von zukunftsfähigen (digital-)technischen Kompetenzen - Schemel, Nele; Schröer, Franz; Tenberge, Claudia (Zukünfte technischer Bildung)

ThorSim: Throughput-Oriented Timing Simulation of FinFET Digital Circuits - Reimer, Jan Dennis; Holst, Stefan; Sadeghi-Kohan, Somayeh; Wunderlich, Hans-Joachim; Hellebrand, Sybille (IEEE International Symposium of Electronics Design Automation (ISEDA'25), May 2025)

Time-resolved momentum microscopy with fs-XUV photons at high repetition rates with flexible energy and time resolution - Schiller, Karl Jakob; Sternemann, Lasse; Stupar, Matija; Omar, Alan; Hoffmann, Martin; Nitschke, Jonah Elias; Mischke, Valentin; Janas, David Maximilian; Ponzoni, Stefano; Zamborlini, Giovanni; Saraceno, Clara Jody; Cinchetti, Mirko (Scientific Reports)
Abstract Time-resolved momentum microscopy is an emerging technique based on photoelectron spectroscopy for characterizing ultrafast electron dynamics and the out-of-equilibrium electronic structure of materials in the entire Brillouin zone with high efficiency. In this article, we introduce a setup for time-resolved momentum microscopy based on an energy-filtered momentum microscope coupled to a custom-made high-harmonic generation photon source driven by a multi-100 kHz commercial Yb-ultrafast laser that delivers fs pulses in the extreme ultraviolet range. The laser setup includes a nonlinear pulse compression stage employing spectral broadening in a Herriott-type bulk-based multi-pass cell. This element allows flexible tuning of the driving pulse duration, providing a versatile time-resolved momentum microscopy setup featuring two operational modes designed to enhance either the energy or time resolution. We show the capabilities of the system by tracing ultrafast electron dynamics in the conduction band valleys of a bulk crystal of the 2D semiconductor WS 2 . Using uncompressed driving laser pulses, we demonstrate an energy resolution better than (107 ± 2) meV, while compressed pulses lead to a time resolution better than (48.8 ± 17) fs.

Tracing the ultrafast buildup and decay of d-d transitions in FePS3 - Nitschke, Jonah Elias; Sternemann, Lasse; Gutnikov, Michael; Schiller, Karl; Coronado, Eugenio; Omar, Alan; Zamborlini, Giovanni; Saraceno, Clara; Stupar, Matija; Ruiz, Alberto M.; Esteras, Dorye L.; Baldoví, José J.; et al. (Newton)

Gestärkt durchs Studium - Universitäre Unterstützungsangebote zum Stress- und Selbstmanagement - Bobe, Julia; Decker, Claudia; Klingsieck, Katrin B.

The Role of Subjective Discomfort in Procrastination - Feeling bad about unnecessary delaying and therefore, preventing it? - Bobe, Julia; Klingsieck, Katrin B.

Analyzing performance portability for a SYCL implementation of the 2D shallow water equations - Büttner, Markus; Alt, Christoph; Kenter, Tobias; Köstler, Harald; Plessl, Christian; Aizinger, Vadym (The Journal of Supercomputing)
SYCL is an open standard for targeting heterogeneous hardware from C++. In this work, we evaluate a SYCL implementation for a discontinuous Galerkin discretization of the 2D shallow water equations targeting CPUs, GPUs, and also FPGAs. The discretization uses polynomial orders zero to two on unstructured triangular meshes. Separating memory accesses from the numerical code allow us to optimize data accesses for the target architecture. A performance analysis shows good portability across x86 and ARM CPUs, GPUs from different vendors, and even two variants of Intel Stratix 10 FPGAs. Measuring the energy to solution shows that GPUs yield an up to 10x higher energy efficiency in terms of degrees of freedom per joule compared to CPUs. With custom designed caches, FPGAs offer a meaningful complement to the other architectures with particularly good computational performance on smaller meshes. FPGAs with High Bandwidth Memory are less affected by bandwidth issues and have similar energy efficiency as latest generation CPUs.

Evaluating oneAPI I/O Pipes in a Case Study of Scaling a SYCL Jacobi Solver to multiple FPGAs - Alt, Christoph; Plessl, Christian; Kenter, Tobias (Proceedings of the 13th International Workshop on OpenCL and SYCL)
In the context of high-performance computing (HPC) for distributed workloads, individual field-programmable gate arrays (FPGAs) need efficient ways to exchange data, which requires network infrastructure and software abstractions. Dedicated multi-FPGA clusters provide inter-FPGA networks for direct device to device communication. The oneAPI high-level synthesis toolchain offers I/O pipes to allow user kernels to interact with the networking ports of the FPGA board. In this work, we evaluate using oneAPI I/O pipes for direct FPGA-to-FPGA communication by scaling a SYCL implementation of a Jacobi solver on up to 25 FPGAs in the Noctua 2 cluster. We see good results in weak and strong scaling experiments.
Keywords: Multi-FPGA; High-level Synthesis; oneAPI; FPGA

Adaptive Spectral Block Floating Point for Discontinuous Galerkin Methods - Sundriyal, Shivam; Büttner, Markus; Alt, Christoph; Kenter, Tobias; Aizinger, Vadym (2025 IEEE High Performance Extreme Computing Conference (HPEC))

Turning to Online Forums for Legal Information: A Case Study of GDPR’s Legitimate Interests - Kyi, Lin; Santos, Cristiana; Ammanaghatta Shivakumar, Sushil; Roesner, Franziska; Biega, Asia (Lecture Notes in Computer Science)

Why Engineering Students Choose a Career in Teacher Education – Qualitative Analysis of Bachelor Students' Motives - Vernholz, Mats; Temmen, Katrin (Towards inclusive and egalitarian vocational education and training: Key challenges and strategies from a holistic and multi-contextual approach. Proceedings of the 6th Crossing Boundaries Conference in Vocational Education and Training)